Brak kanonu i resentyment współczesnego humanisty - Doda-Wyszyńska, Agnieszka (Człowiek i Społeczeństwo, 2020)
A canon is a word of religious origin. It constituted a basic aim of education at the university level. However, that time came to an end when the idea of universality was replaced with the idea of perfection (implicitly a clerk-like perfection). Ressentiment (a repressed feeling, described by Nietzsche and later by Scheler) acts against a higher ability to enjoy cultural pleasure; it creates a contemporary human as a man of labour and utility who cannot make use of the so-called cultural assets (from the canon). Depending on which field the idea of a canon refers to, we will understand it as such. It is most associated with art where it functions as a set of models, rules and methods of creation current in a given period of culture. There are three semantic fields of the background needed to examine the notion of a canon: culture, time and space (I dedicated two chapters of the paper to each). Today, a humanist has completely new roles, since not only did culture change but also time and space – the basic “forms of sensuality”, which Kant defined as our main point of orientation and a ground for thinking about the world. Coping with the canon was mainly intended to teach good choices, not only the choices regarding texts. It may be the most important mission of humanists: to show the canon and teach how to choose one of our own. Now we are observing a kind of fear of the canon (Bloom). We are irritated with what we cannot understand. The biggest load of ressentiment lies within society, in which social equality, both political and formal, goes hand in hand with very large discrepancies in terms of actual power, wealth and education. Today, humanist reflection on culture even left the political level, related to knowledge, and entered a lower, more fundamental level connected with satisfying basic needs. The only role of a contemporary “humanist” is to free themself of illusions, i.e. also of the excess of texts. Our globalised space is ruled by quick rankings and summaries of texts. We lost the need to which art responded – to determine the eternal perspective of life.